Predictors of incomplete viral response and virologic failure in patients with acute and early HIV infection. Results of Italian Network of ACuTe HIV InfectiON (INACTION) cohort. Issue 8 (24th June 2020) - Taramasso, L; Fabbiani, M; Nozza, S; De Benedetto, I; Bruzzesi, E; Mastrangelo, A; Pinnetti, C; Calcagno, A; Ferrara, M; Bozzi, G; Focà, E; Quiros‐Roldan, E; et al.
Abstract : Objectives: The aim of this study was to evaluate the factors that can influence an incomplete viral response (IVR) after acute and early HIV infection (AEHI). Methods: This was a retrospective, observational study including patients with AEHI (Fiebig stages I–V) diagnosed between January 2008 and December 2014 at 20 Italian centres. IVR was defined by: (1) viral blip (51–1000 HIV‐1 RNA copies/mL after achievement of < 50 HIV‐1 RNA copies/mL); (2) virologic failure [> 1000 copies/mL after achievement of < 200 copies/mL, or ≥ 200 copies/mL after 24 weeks on an antiretroviral therapy (ART)]; (3) suboptimal viral response (> 50 copies/mL after 48 weeks on ART or two consecutive HIV‐1 RNA levels with ascending trend during ART). Cox regression analysis was used to calculate the hazard ratios (HRs) and 95% confidence intervals (95% CIs) for IVR. Results: In all, 263 patients were studied, 227 (86%) males, with a median [interquartile range (IQR)] age of 38 (30–46) years. During a median follow‐up of 13.0 (5.7–31.1) months, 38 (14.4%) had IVR. The presence of central nervous system (CNS) symptoms was linked to a higher risk of IVR (HR = 4.70, 95% CI: 1.56–14.17), while a higher CD4/CD8 cell count ratio (HR = 0.13, 95% CI: 0.03–0.51 for each point increase) and first‐line ART with three‐drug regimens recommended by current guidelines (HR = 0.40, 95% CI: 0.18–0.91 compared with other regimens including four or five drugs, older drugs or non‐standard backbones) were protective against IVR. Conclusions: Patients with lower CD4/CD8 ratio and CNS symptoms could be at a higher risk of IVR after AEHI. The use of recommended ART may be relevant for improving short‐term viral efficacy in this group of patients.